2015
DOI: 10.1021/jacs.5b01791
|View full text |Cite
|
Sign up to set email alerts
|

Proton-Coupled Electron Transfer Dynamics in the Catalytic Mechanism of a [NiFe]-Hydrogenase

Abstract: The movement of protons and electrons is common to the synthesis of all chemical fuels such as H2. Hydrogenases, which catalyze the reversible reduction of protons, necessitate transport and reactivity between protons and electrons, but a detailed mechanism has thus far been elusive. Here, we use a phototriggered chemical potential jump method to rapidly initiate the proton reduction activity of a [NiFe] hydrogenase. Coupling the photochemical initiation approach to nanosecond transient infrared and visible ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
210
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(229 citation statements)
references
References 64 publications
(109 reference statements)
16
210
1
Order By: Relevance
“…Previously, we have shown that the reverse EPT process, probed by photoreduction of Ni a -S, correlates with pH in the same way, in both rate and KIE. 33 These observations suggest a common residue responsible for the forward and reverse EPT, with both mechanisms involving significant nuclear tunneling. 33 It is clear from the kinetic data that at least one Ni a -I state is an intermediate in the conversion of Ni a -S and Ni a -C. Three potential mechanisms could explain the connection of the Ni a -I states to Ni a -S and Ni a -C: (1) a serial mechanism in which both Ni a -I 1 and Ni a -I 2 are on-pathway intermediates between Ni a -S and Ni a -C, (2) a parallel mechanism in which one Ni a -I state is an intermediate and the other is an off-pathway species, or (3) a hybrid mechanism in which one Ni a -I state is an intermediate but is in rapid equilibrium with an off-pathway state (the other Ni a -I state) (Figures S13 and S14 of the Supporting Information).…”
Section: ■ Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Previously, we have shown that the reverse EPT process, probed by photoreduction of Ni a -S, correlates with pH in the same way, in both rate and KIE. 33 These observations suggest a common residue responsible for the forward and reverse EPT, with both mechanisms involving significant nuclear tunneling. 33 It is clear from the kinetic data that at least one Ni a -I state is an intermediate in the conversion of Ni a -S and Ni a -C. Three potential mechanisms could explain the connection of the Ni a -I states to Ni a -S and Ni a -C: (1) a serial mechanism in which both Ni a -I 1 and Ni a -I 2 are on-pathway intermediates between Ni a -S and Ni a -C, (2) a parallel mechanism in which one Ni a -I state is an intermediate and the other is an off-pathway species, or (3) a hybrid mechanism in which one Ni a -I state is an intermediate but is in rapid equilibrium with an off-pathway state (the other Ni a -I state) (Figures S13 and S14 of the Supporting Information).…”
Section: ■ Discussionmentioning
confidence: 97%
“…33 The Ni a -C state (green curve), which was spectrally distinct from the other resonances in the CO region, remained present at all pH values and represented the dominant state of the enzyme. In addition to the Ni a -C state, signatures of Ni a -S (red curve at ∼1949 cm −1 ) and Ni a -SR (blue curve at ∼1954 cm −1 ) were observed.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…The Ni-SI:H 2 complex corresponds the Michaelis complex essentially used in the enzyme kinetics. B. L. Greene et al have also assumed the presence of H 2 -complex with Ni-SI state in the enzyme kinetic analysis [48]. Considering the Ni-SI:H 2 complex formation and a steady-state approximation, the steady-state catalytic current of the HmMBH-catalyzed H 2 oxidation (i cat ) in the presence of excess amounts of H 2 can be expressed by Eq.…”
Section: Nernst Analysis On the [Nife]-active Site Of Hmmbhmentioning
confidence: 99%